Perancangan Aplikasi Kamus Bahasa Indonesia-Sentani Berbasis Android - Agung Dwi Saputro; Feby Seru (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Sentani is one of the regional languages in Papua which is experiencing a shift and signs of extinction due to the decreasing number of speakers and no longer being used in both formal and informal forums. Even many Sentani children who live on villages far from urban areas are starting don’t understand the Sentani language. The aim of this research is to create an Android-based Indonesian-Sentani dictionary application that can be used as a learning tool. The research method used in this research is a qualitative method that focuses on a case study of creating a Sentani language dictionary application. The research began by collecting data consisting of observation, interviews and literature study.